2011
DOI: 10.2478/s11536-011-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined hormone contraceptive choice experience in Czech Republic

Abstract: AbstractThe aim of the prospective, multicenter project was to evaluate the effect of standardized information on the decision of woman when selecting application routes for combined hormonal contraceptives (CC). Selection the route of CC’s administration before and after consultation with the physician was evaluated on the group of 1326 women in 125 centres in the Czech Republic using a questionnaire. Analysis of the difference between the intended (4,1%) and selected (33,9%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Summary characteristics of the included articles are provided in the study description table, organized by geographic WHO region ( Tables 1A – 1F ). The Contraceptive Health Research of Informed Choice Experience (CHOICE) study, a large European multicountry study, was reported in 10 articles [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] 29 ], and the Contraceptive CHOICE study on long-acting reversible contraceptive (LARC) methods in Missouri, the United States of America (USA), was reported in 4 articles [ [30] , [31] , [32] 33 ]. The 410 studies (reported in 423 articles) included 463,048 participants; individual study sample sizes ranged from 10 (a qualitative study on intrauterine devices (IUDs) in the United Kingdom [34] ) to 70,016 (a cross-sectional analysis of a national household survey in India [35] ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary characteristics of the included articles are provided in the study description table, organized by geographic WHO region ( Tables 1A – 1F ). The Contraceptive Health Research of Informed Choice Experience (CHOICE) study, a large European multicountry study, was reported in 10 articles [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] 29 ], and the Contraceptive CHOICE study on long-acting reversible contraceptive (LARC) methods in Missouri, the United States of America (USA), was reported in 4 articles [ [30] , [31] , [32] 33 ]. The 410 studies (reported in 423 articles) included 463,048 participants; individual study sample sizes ranged from 10 (a qualitative study on intrauterine devices (IUDs) in the United Kingdom [34] ) to 70,016 (a cross-sectional analysis of a national household survey in India [35] ).…”
Section: Resultsmentioning
confidence: 99%
“…Among women choosing between the pill, patch, and ring in the European CHOICE study [ 23 , 25 , 26 ], intensive counseling significantly decreased the proportion of undecided women and significantly increased the proportion of women choosing the ring (from less than 10% pre-counseling to 23.8%–42.6% postcounseling, p < 0.001) though pill and patch intention/usage remained fairly consistent (around 50% and less than 10% respectively). Women who stayed with oral contraceptive pills cited ease of use and familiarity as their primary reasons, while women who switched to the patch and ring cited reasons like ease of use, decreased frequency of use (and thus less opportunity to forget, i.e., lower probability of omission), and effectiveness when experiencing vomiting/diarrhea/illness.…”
Section: Resultsmentioning
confidence: 99%
“…In coupled women, the choice of contraceptive type may be related to other variables. For example, factors such as plans for conception, preferences for the method of application (e.g., a relatively high percentage of parous women in our sample used non-hormonal IUD), and individual tolerance of various OC types ( Fait, 2011 ) could determine the choice of contraceptive method.…”
Section: Discussionmentioning
confidence: 99%